Antineoplastic effects of 4 homoeopathic medicines - Maliekal, Thobias P. (British Homeopathic Journal, 1997)
The present work is concerned with the study of the antitumour activities of the 4 homoeopathic medicines Kali muriaticum, Phytolacca decandra, Hydrastis canadensis and Zincum metallicum in murine models. The experiments showed that the administration of Zincum met 200x considerably increased the life span of the tumour-bearing mice.